Pengaruh Net Profit Margin Dan Rasio Biaya Operasional Pendapatan Operasional Terhadap Kemampuan Zakat - Sitompul, Fitri Purnama Sari; Siregar, Fatahuddin Aziz; Nasution, Ja'far (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2020)
Zakah is one of the social activities carried out by PT. Bank Syariah Mandiri and those who are required to be paid when they reach the nisab. The calculation of zakah funds issued is 2.5% of profit before tax. To find out the ability of a bank to generate relative profits using Net Profit Margin (NPM) and the ratio of Operating Costs to Operating Income based on data obtained from PT. Bank Syariah Mandiri. This research was conducted to determine whether NPM and BOPO affect the zakat ability of PT. Bank Syariah Mandiri both partially and simultaneously. This research is a quantitative study with secondary data with data analysis techniques using multiple linear regression methods. The results of the research partially (t test) state that, NPM has no effect on Zakah. Meanwhile, BOPO has an effect on zakah. NPM and BOPO together have an influence on zakah. Keywords: Net Profit Margin (NPM), and the ratio of Operating Costs to Operational Income (BOPO) Against Zakah.